Crucial Factors in Selecting Information as A Part of Travel Planned Behavior (TPB): A Researched Guideline For Service Providers in Tourism - Iris MIHAJLOVIĆ (Communications of International Proceedings, 2024)
This paper emphasizes the theoretical approach to the first step in decision making process of travelling, choosing an optimal way of communication.  Putting an emphasis on driving factors in Travel Planned Behavior (TPB), researched tiers and issues, former void in literature has made this area of ​​research both - necessary and indispensable, The paper considers numerous advantages and additional values resulting from the application of modern tools used by service providers and intermediaries. This is confirmed as perceived, the most useful source when informing and delivering accurate information, due to speed, the possibility of comparison, coverage, availability and usefulness in terms of saving time. This could stimulate further transformational processes in business, primarily in communication, creation and delivering products.  Behavior and interests, of tourists are very important when choosing modalities of travel.  Developmental modalities the level of use of digital tools have been pointed in numerous studies. Perceiving experiences driven by those studies could be connected with time of travel, selection of travel motives that define activities, contents and organization of travel in accordance with the price. The methodology used in the study supports secondary research, while the research question is based on the monitoring of market requirements as the reflection of structural qualitative changes in tourist demand. Findings as a researched guidelines represent recommendations to service providers in terms of delivering and sharing information, putting an emphasis on the role and the importance of personal experiences of service users (travelers), as well as digital tools that encourage more efficient and rational time management.
Keywords: Keywords: ICT; digitalization; time; sources of information; special needs